Resolving Electrode Morphology’s Impact on Platinum Group Metal-Free Cathode Performance Using Nano-CT of 3D Hierarchical Pore and Ionomer Distribution - Komini Babu, Siddharth; Chung, Hoon T; Zelenay, Piotr; Litster, Shawn (ACS applied materials & interfaces, 2016)
This article reports on the characterization of polymer electrolyte fuel cell (PEFC) cathodes featuring a platinum group metal-free (PGM-free) catalyst using nanoscale resolution X-ray computed tomography (nano-CT) and morphological analysis. PGM-free PEFC cathodes have gained significant interest in the past decade since they have the potential to dramatically reduce PEFC costs by eliminating the large platinum (Pt) raw material cost. However, several challenges remain before they are commercially viable. Since these catalysts have lower volumetric activity, the PGM-free cathodes are thicker and subject to increased gas and proton transport resistances that reduce the performance. To better understand the efficacy of the catalyst and improve electrode performance, a detailed understanding the correlation between electrode fabrication, morphology, and performance is crucial. In this work, the pore/solid structure and the ionomer distribution was resolved in three dimensions (3D) using nano-CT for three PGM-free electrodes of varying Nafion loading. The associated transport properties were evaluated from pore/particle-scale simulations within the nano-CT-imaged structure. These characterizations are then used to elucidate the microstructural origins of the dramatic changes in fuel cell performance with varying Nafion ionomer loading. We show that this is primarily a result of distinct changes in ionomer’s spatial distribution. The significant impact of electrode morphology on performance highlights the importance of PGM-free electrode development in concert with efforts to improve catalyst activity and durability.